IMPLEMENTASI PROGRAM REVITALISASI TPQ DAN AKTIVASI KEGIATAN YASINAN: UPAYA PENGUATAN PENDIDIKAN AGAMA - Nopita, Yanti; Maidawilis, Maidawilis; Pradeska, Eca; Yuhannes, Febi; Wulandari, Miken; Ikhsan, Miktahul; Nurambiya, Nurambiya; Jannah, Raudatul; Arpadila, Winda; Putri, Yuni Eka; Waldina, Zefanya Fathiha; Witri, Zuhdatul Qanita (Ensiklopedia of Journal, 2025)
This Community Service (PKM) aims to revitalize the Taman Pendidikan Al-Qur'an (TPQ) and the activation of Yasinan gatherings in Nagari Pasia Laweh as part of the Universitas Negeri Padang’s community service program (KKN). A descriptive qualitative approach was used, focusing on participatory observation and documentation. The TPQ revitalization included environmental cleaning, playful learning methods, and more effective time management. The Yasinan gatherings were aimed at strengthening social bonds among villagers. Findings reveal increased participation among children in TPQ activities and higher attendance in Yasinan by local women. In conclusion, the TPQ revitalization and Yasinan reactivation successfully fostered a more positive learning environment and social interactions in Pasia Laweh.Keywords: TPQ Revitalization, Yasinan, Pasia Laweh, Community Service, Social Interaction